2012
DOI: 10.1177/145749691210100302
|View full text |Cite|
|
Sign up to set email alerts
|

Nasoenteric Tube Complications

Abstract: the use of nasoenteric tubes (Nets) is ubiquitous, and clinicians often take their placement, function, and maintenance for granted. Nets are used for gastrointestinal decompression, enteral feeding, medication administration, naso-biliary drainage, and specialized indications such as upper gastrointestinal bleeding. morbidity associated with Nets is common, but frequently subtle, mandating high index of suspicion, clinical vigilance, and patient safety protocols. common complications include sinusitis, sore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 76 publications
1
65
0
7
Order By: Relevance
“…Ultrasonography [30] Ph indicator [36,37] Stridor [47] Pulmonary aspiration [50] Sort maneuver [22,23] Airway scope [31] Electromagnetic device [38] Pneumothorax [51] Nelaton [32] Chemical assessment of aspirates (Ph, trypsin, bilirubin, CO 2 and pepsin) [39,40] Perforation of lamina cribrosa [52] Tube length End tidal CO 2 monitoring [41] Retropharyngeal abcess [47] Fluroscopy [42] Stricture formation Endoscopy [42] Aortoesophageal fistula [52] Manometer [43,44] Nasogastric tube syndrome [53,54] (TEE) probe insertion (See video at: http://atlasofscience. org/nasogastric-tube-insertion-the-simple-yet-impossible/ accessed 11 Nov 2016).…”
Section: By Equipment Minor Majormentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasonography [30] Ph indicator [36,37] Stridor [47] Pulmonary aspiration [50] Sort maneuver [22,23] Airway scope [31] Electromagnetic device [38] Pneumothorax [51] Nelaton [32] Chemical assessment of aspirates (Ph, trypsin, bilirubin, CO 2 and pepsin) [39,40] Perforation of lamina cribrosa [52] Tube length End tidal CO 2 monitoring [41] Retropharyngeal abcess [47] Fluroscopy [42] Stricture formation Endoscopy [42] Aortoesophageal fistula [52] Manometer [43,44] Nasogastric tube syndrome [53,54] (TEE) probe insertion (See video at: http://atlasofscience. org/nasogastric-tube-insertion-the-simple-yet-impossible/ accessed 11 Nov 2016).…”
Section: By Equipment Minor Majormentioning
confidence: 99%
“…Parotitis, perforation of lamina cribrosa and retropharyngeal abscess are other complications related to NGT [47,84]. Moreover, there have been some reports about the stricture formation, aortho-esophageal fistula and submucosal passage [52]. Brousseau et al [53] reported a rare but life threatening complication of NGT which is characterised by bilateral vocal cord paralysis and supraglottic oedema following NGT insertion.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the overall literature on the topic is relatively scant, there is a significant association between NETs and sinusitis (Prabhakaran et al 2012). There seems to be a spectrum of clinical and subclinical sinus involvement in the patient Fig.…”
Section: Delayed Complications Sinusitismentioning
confidence: 99%
“…Independent risk factors for sinusitis in the intensive care setting include nasal colonization with enteric gram-negative bacilli, sedation, depressed mental state (i.e., GCS >7), and feeding via NET (George et al 1998). Based on this information, minimizing the NET dwelling times is perhaps the best preventive strategy and may also help reduce the risk of pressure-related injuries to the nasal area as well as erosive changes associated with mucosal irritation (Prabhakaran et al 2012).…”
Section: Delayed Complications Sinusitismentioning
confidence: 99%